Proceso atención de enfermería en paciente adulto mayor con tumor maligno del pulmón. - Cornejo Zamora, Alexandra Elizabeth (2023)
The following case study will focus on lung cancer in an older person, its management, and methods that can help them live a healthier life. Lung cancer is the most common cause of death compared to other types of cancer, and its symptoms may include coughing, malaise, weight loss, and to a lesser degree hemoptysis. Chest X-rays or CT scans can diagnose it, and a biopsy can confirm the diagnosis. Surgery can also be done, but that depends on how advanced the disease is. Median survival is about 5 years, depending on the patient, and treatment is based on surgery, chemotherapy, radiotherapy, or a combination of all of them. Exposure to toxins and smoking, two other potential risk factors, increase the risk of lung cancer.